2014
DOI: 10.1021/jp508389u
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Solvent Dynamics in Nanoscopic Silica Sol–Gel Glass Pores by 2D-IR Spectroscopy of an Intrinsic Vibrational Probe

Abstract: Porous sol–gel matrices were synthesized with IR-active Si–H vibrational chromophores integrated into the silica network. The Si–H vibrational mode was found to be highly accessible to solvents within the nanoscopic pores. Vibrational solvatochromism of the silane vibration was controlled largely by interactions between infiltrating solvents and the oxygen and hydroxide sites in the silica. Exchanging solvents in the silica matrices produced reversible solvatochromic shifts in some cases but led to irreversibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 111 publications
0
32
1
Order By: Relevance
“…Previous analysis showed that the hydrogen bonding ability of the solvent was correlated with solvatochromic shifts of ν Si-H on silanes and silica sol-gels. 71 Consequently, we hypothesized that the solvent interactions with the oxygen atoms would have the greatest influence on the vibrational mode due to the inductive effect. 71,72 Yet, the fact that the solvatochromic trend in Fig.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous analysis showed that the hydrogen bonding ability of the solvent was correlated with solvatochromic shifts of ν Si-H on silanes and silica sol-gels. 71 Consequently, we hypothesized that the solvent interactions with the oxygen atoms would have the greatest influence on the vibrational mode due to the inductive effect. 71,72 Yet, the fact that the solvatochromic trend in Fig.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…71 Consequently, we hypothesized that the solvent interactions with the oxygen atoms would have the greatest influence on the vibrational mode due to the inductive effect. 71,72 Yet, the fact that the solvatochromic trend in Fig. 1 is the same for TriPS, which lacks oxygen atoms in its ligands, indicates that the solvent influence is not limited to this specific interaction.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Infrared absorption and Raman spectroscopies offer two approaches to characterizing the structure and inherent disorder of silicon surfaces. ,, Single crystal and amorphous silicon materials are commonly hydrogen-passivated to eliminate defects and improve their electronic properties . This results in surfaces that are covered with monohydride (R 3 Si–H) and polyhydride (R 2 Si–H 2 and RSi–H 3 ) vibrational modes that are sensitive to their local chemical environments. , Surface adsorption, desorption, and functionalization depend largely on the vibrational lifetime of these surface modes, , whose relaxation dynamics are often dominated by defects . Lyding and coworkers reported that hot electron degradation in silicon transistors was up to 50 times slower for deuterium-passivated surfaces, leading to enhanced carrier transport as a direct result of a shorter Si-D vibrational lifetime .…”
Section: Introductionmentioning
confidence: 99%
“…In a departure from this passive role, our group recently showed that a silicon hydride vibration on the silica surface could be used to probe the structural dynamics of molecular guests within the pore volume. 21,22 Rather than relying upon the spectroscopy of the infiltrating solvent or solute, or a chemically bound sensitizer, this approach transforms the silica matrix itself into a general sensing platform to monitor any infiltrating species.…”
Section: ■ Introductionmentioning
confidence: 99%
“…28−31 The ν Si−H can also be solvatochromic to varying degrees depending on silicon functionalization; solvatochromic shifts are enhanced when oxygen atoms are the nearest neighbor species, as in the case of silica. 22 In addition, the vibrational peak shape is affected by time dependent structural changes in the proximal solvation volume. 21,22 The effects of sol−gel aging on a number of spectroscopic parameters have been studied, 25,32−36 but its influence on the vibrational characteristics of surface vibrational modes remains unexplored.…”
Section: ■ Introductionmentioning
confidence: 99%